Student engagement in university decision-making and governance : towards a more systemically inclusive student voice 2015-2016 : final report. - Varnham, Sally; Olliffe, Bronwyn; Waite, Katrina; Cahill, Ann (Australia. Dept of Education and Training (DET), 2018)
This project continued a collaborative investigation into the case for a more systemically inclusive student voice in decision-making and governance in Australian universities. This investigation was driven by the need for a deep consideration of the meaningful and effective engagement of students' views at all levels and of all cohorts, and how this may enhance the quality and standards of the institution and the student's university experience. It drew on international experience and current practice in Australia to ask: What is 'student engagement' leading to 'student partnership' in university decision-making, Why may student engagement processes warrant consideration in today's higher education environment, in terms of value to universities, their students and to the sector as a whole, How may student engagement be embedded most effectively in university policies and processes to enable the development of a culture of student voice. The project drew on international experience and evolving examples of good practice in Australia to stimulate a conversation about student representation. This report is part of a set of four publications produced by Professor Varnham and her team that explore and promote the benefits of student engagement in university decision-making and governance. The other publications are a report on international investigations, a good practice case-studies report and a survey report. [Executive summary, ed]